Folklore in Utah: a history and guide to resources - Stanley, David, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2004)
Over thirty scholars examine the development of folklore studies through the lens of over one hundred years of significant activity in a state that has provided grist for the mills of many prominent folklorists. In the past the Folklore Society of Utah has examined the work of such scholars in biographical and other essays published in its newsletters. This book incorporates those essays and goes well beyond them to include many other topics, offering a thorough history of folklore studies and a guide to resources for those pursuing research in Utah now and in the future. The essays survey the development and contributions of folklore studies in Utah from 1892 to 2004 but also represent developments in both academic and public-sector folklore throughout the United States. Following a thorough historical introduction, part I profiles the first folklorists working in the state, including Hector Lee, Thomas Cheney, Austin and Alta Fife, Wayland Hand, and Lester Hubbard. Part II looks at the careers of prominent Utah folklorists Jan Harold Brunvand, Barre Toelken, and William B. Wilson, as well as the works of the next, current generation of folklorists. Part III covers studies in major folklore genres, with essays on the study of material culture, vernacular architecture, and Mormon, ethnic, Native American, and Latino folklore. Part IV examines public folklore programs including organizations, conferences, and tourism. Back matter describes academic programs at Utah institutions of higher education, summarizes the holdings of the various folklore archives in the state, and provides a complete cross-indexed bibliography of articles, books, and recordings of Utah folklore.
Preface / David Stanley -- Folklore work in Utah--a historical survey / David Stanley -- PART I: The first folklorists -- Folklore and the literary generation of the 1930s / Edward A. Geary -- Hector Lee / David Stanley -- Folklore and a Utah childhood / Hector Lee -- Wayland Hand--Utah folklorist, international scholar / Barre Toelken -- Austin and Alta Fife, pioneer folklorists / William A. Wilson -- Lester Hubbard and the folksongs of Utah / Hal Cannon -- Thomas Cheney and the dilemmas of Mormon folklore / George H. Schoemaker -- Olive Woolley Burt, collector of murder ballads / Anne Reichman -- Helen Papanikolas, folklorist of ethnicity / Yiorgos Anagnostou -- PART II: The second and third generations of folklorists -- "On being human": the legacy of William A. Wilson / George H. Schoemaker -- Barre Toelken, folklorist of culture and performance / Matthew Irwin -- Jan Harold Brunvand and the urban legend / Jacqueline S. Thursby -- The third generation of Utah folklorists / Michael Christensen -- PART III: Studies in Utah folklore and folklife -- Native American folklore studies / Kathryn L. MacKay -- Mormon folklore studies / Jull Terry Rudy -- J. Golden Kimball narratives / Erica A. Eliason -- Latino folklore studies / Sarah M. Rudd -- Ethnic folklore studies / Philip F. Notarianni -- Material culture studies / Carol A. Edison -- Studies in Utah vernacular architecture / Thomas Carter -- PART IV: Public programs -- Public folklore in Utah / Elaine Thatcher -- Under the big top: the Utah Humanities Council and folklore / Anne F. Hatch -- Ethnic organizations and the maintenance of tradition / Craig R. Miller -- The Folklore Society of Utah / David Stanley -- Lessons of summer: The Fife Folklore Conference / Barbara Lloyd -- Cultural tourism in Utah / Julie Hartley -- Folklore in Utah's state and national parks / Karen Krieger.
Keywords: Folklore -- Utah -- History; Folklorists -- Utah -- Biography; Folklore -- Study and teaching (Higher) -- Utah -- History; Utah -- Folklore; Utah -- Social life and customs